P0346THE EFFECTS OF RITUXIMAB MAINTENANCE THERAPY ON LUPUS NEPHRITIS. (6th June 2020) - Cassia, Matthias; Jones, Rachel B; Cagna, Daniele; Smith, Rona; Casazza, Giovanni; Jeannin, Guido; Zani, Roberta; Moroni, Gabriella; Sinico, Renato A; Emmi, Giacomo; Vaglio, Augusto; Gallieni, Maurizio; et al.
Abstract: Background and Aims: Lupus Nephritis (LN) is the organ manifestation with the most severe prognosis in Systemic Lupus Erythematosus (SLE). Treatment options are limited due to partial efficacy, intolerance or side effects; moreover 10% of patients reach ESRD despite treatments. Rituximab (RTX) in LN is recommended as second line drug for induction of the remission after failure of Cyclophosphimide or Mycophenolate Mofetil. We have shown a role for RTX as maintenance therapy (RMT) in SLE however the effects of such approach on LN are still unclear. Aim of this study was a sub-analyses of a cohort of SLE patients treated with RTX focusing on the ones with active LN at the moment of the first RTX administration. Methods: Patients with active LN at the time of the first RTX administration within a cohort of 147 patients with SLE were identified. Patients with SLE and a flare of LN were classified as treated with a "Single RTX course" (any RTX regimen administered within a single month) (SRC) or with RMT. Patients receiving at least three SRCs with the aim of relapse prevention and within 4 to 8 months between consecutive treatments, were classified as receiving RMT. LN activity was determined according to creatinine, proteinuria and haematuria; complete response (CR) was defined as a decrease of proteinuria to <0.5 g/day, normal creatinine and negative urinary sediment; partial response (PR) was defined as ≥50% improvement in creatinine and proteinuria, treatment failure (TF) was any other condition. A renal flare (RF) was defined as an increase of creatinine and/or proteinuria >30% or the detection of an active urinary sediment due, according to the treating physician, to active disease. Results: 33 patients were identified; a renal biopsy had been performed in 76% with prevalence of class IV lupus nephritis in 16/33 (48%). Six months after RTX the rate of CR, PR and TF was respectively 36%, 27% and 36%; proteinuria and the prednisolone dose reduced significantly compared to baseline (respectively from a median of 2200 mg/day (IQR 499-5400) to 850 mg/day (IQR 400-1700) (p=0.005)) and from 25 mg (IQR 11-25) to 10 mg (IQR 6.125-15) (p<0.0001)). At univariate analyses the only factor associate to the risk of TF was a high number of immunosuppressive drugs employed before RTX (p=0.0077). Of the 33 patients, 11 received RMT with a median duration of 18 months (IQR 12, 6-23, 4) and a median RTX dose of 5 g (IQR 4-6). During the RMT 3 patients experienced a renal flare. The median follow-up after the last RTX administration within the SRC and the RMT groups was respectively 15 months (IQR 13, 5-18, 4) and 16 months (IQR 3, 5-23). Comparing the RF free-survival of the two subgroups after the last RTX infusion, there was a trend towards a longer relapse free survival after the RMT (p=0.057) ( figure, left panel) . Of interest, the renal relapse free-survival of the 11 patients treated with RMT after the last RTX infusion was significantly longer compared to the one of the same group after the first RTX (p=0.0271) ( figure, right panel) . The incidence of SAEs per 100 patient years was 0.31 in the SRC group and 0.74 in the RMT group. Conclusion: RTX is confirmed as an effective option for patients with LN. A RMT may have a role in improving LN disease control compared to a single RTX administration.